FETOMATERNAL OUTCOME OF PREGNANCY WITH DENGUE INFECTION (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Dengue is a vector born viral infection. Dengue fever during pregnancy is associated with early pregnancy failure, preterm delivery, low birth weight babies, prematurity and occasionally neonatal mortalities. The aim of the study was to know the clinical profile, maternal and fetal outcome of dengue fever during pregnancy.Objective: To study the impact of dengue fever on the natural course of pregnancy and labor as well as on neonates.Materials & Method: A prospective study was carried out from the month of May to October 2018 (monsoon and post monsoon season) over a period of six months which has included all pregnant patients irrespective of period of gestation and who have been admitted with fever and features suggestive of dengue infection at tertiary care teaching hospital.Results: Out of the 120 pregnant patients admitted with suspected dengue infection, 30 were diagnosed serologically with dengue. Fever with generalized myalgia was found in 73.3% patients and Thrombocytopenia was found in 42.3% patients. Fortunately no maternal mortality was there in present series, but 6.6% were still born and 16.6% of the babies required NICU admission due to prematurity and low birth weight.Conclusions: Pregnancy with dengue infection is a great high risk factor for maternal and fetal wellbeing. Outcome is correlated not only with gestational age but also the severity of clinical manifestations due to viral load at the time of occurrence of dengue fever. With high index of suspicion, prompt diagnosis and management help to improve fetomaternal outcome.
Keywords: Dengue fever; Fetomaternal outcome; Tertiary care teaching hospital